Human Rights and Emerging Technologies in India: Legal Perspectives on Human Embryonic Stem Cell Research. - Rahi Samuel Alhat (International Journal of Medical Toxicology and Legal Medicine, 2024)
Human rights and technology share a complex relationship, and the introduction to research in human embryonic stem cell (hESC) research in India has paved the way for more complexity. The article studies the relationship between human rights and technologies, with a particular concentration on human embryonic stem cell research. It explores the legal, ethical, and societal dimensions of hESC research, emphasizing the importance of upholding human rights while navigating the complexities of scientific progress. The article briefly discusses the implications and effects of guidelines provided by the Indian Council of Medical Research (ICMR) and their connection with the international framework. While studying these aspects, research has tried to establish a nexus between ethics and human rights. In conclusion, the article emphasizes the importance of balancing scientific innovation with ethical principles and human rights in the pursuit of hESC research in India. In conclusion, the article summarizes key findings regarding the intersection of human rights, emerging technologies, and hESC research in India and underscores the importance of upholding human rights principles while advancing scientific innovation in the legal landscape.